2007
DOI: 10.1007/s00213-007-0905-x
|View full text |Cite
|
Sign up to set email alerts
|

The CRF1 receptor antagonist antalarmin attenuates yohimbine-induced increases in operant alcohol self-administration and reinstatement of alcohol seeking in rats

Abstract: These results suggest that extrahypothalamic CRF1 receptors are involved in the effect of yohimbine on operant alcohol self-administration and on relapse to alcohol seeking and support the notion that CRF1 receptor antagonists should be considered in alcohol addiction treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
187
2
6

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 175 publications
(219 citation statements)
references
References 90 publications
24
187
2
6
Order By: Relevance
“…However, it has been shown that the progesterone metabolite, allopregnanolone, can have both a stimulatory or inhibitory effect on ethanol intake depending on the dose administered and the drinking paradigm used (Ford et al, 2005;Janak et al, 1998;Morrow et al, 2001). Our group and others (Marinelli et al, 2007) have previously shown that yohimbine produces significant increases in circulating CORT levels and, in the present study, we show that yohimbine administration in ethanol-extinguished rats causes a nonsignificant increase in progesterone levels (Supplementary Figure 1). However, the levels in the male rats described here remain very low and are quite close to basal levels reported in the literature (Andersen et al, 2004(Andersen et al, , 2005Auger et al, 2006).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…However, it has been shown that the progesterone metabolite, allopregnanolone, can have both a stimulatory or inhibitory effect on ethanol intake depending on the dose administered and the drinking paradigm used (Ford et al, 2005;Janak et al, 1998;Morrow et al, 2001). Our group and others (Marinelli et al, 2007) have previously shown that yohimbine produces significant increases in circulating CORT levels and, in the present study, we show that yohimbine administration in ethanol-extinguished rats causes a nonsignificant increase in progesterone levels (Supplementary Figure 1). However, the levels in the male rats described here remain very low and are quite close to basal levels reported in the literature (Andersen et al, 2004(Andersen et al, , 2005Auger et al, 2006).…”
Section: Discussionsupporting
confidence: 80%
“…We also found that the high dose of mifepristone can block yohimbine-induced reinstatement of sucrose-seeking when delivered systemically, but not into the CeA. It has previously been shown that yohimbineinduced reinstatement of ethanol-seeking can be modulated by many receptors, including: CRF (Marinelli et al, 2007), orexin (Richards et al, 2008), serotonin (Le et al, 2009), neuropeptide Y (Cippitelli et al, 2010), peroxisome proliferator-activated receptor-g (Stopponi et al, 2011), adrenoreceptors (Le et al, 2011), and delta-opioid receptors (Nielsen et al, 2011). This study is the first, to our knowledge, to indicate that GRs play a role in the reinstatement behavior elicited by yohimbine.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…In addition, Yohimbine, which provokes stress-and anxiety-like behaviors in both humans and rodents, increased operant ethanol self-administration. Yohimbine-induced reinstatement of alcohol seeking was attenuated by the corticotrotropin-releasing factor 1 (CRF1) receptor antagonist antalarmin (Marinelli et al 2007). More importantly, preclinical evidence with pharmacological therapies targeting CRF receptor (CRF-R) signaling were involved in the regulation of neurobiological responses to ethanol; CRF-R antagonists protect against increased ethanol intake and relapse-like behaviors precipitated by exposure to a stressful event [for review see Lowery and Thiele 2010].…”
Section: Consequences Of Csc On Body Weight Gain and Anxiety-like Behmentioning
confidence: 99%